DNA gyrase: purification and catalytic properties of a fragment of gyrase B protein. - Gellert, M (1979)
A protein isolated from Escherichia coli complements the DNA gyrase A (NalA) protein to generate an activity that relaxes supercoiled DNA. Oxolinic acid, a known inhibitor of DNA gyrase, blocks this activity and causes double-strand cleavage of DNA at the same sites as are attacked by DNA gyrase. The protein, of molecular weight 50,000, appears to be fragment of the DNA gyrase B (Cou) protein (molecular weight, 90,000) as judged by the identical sizes of numerous peptides produced by partial proteolytic digestion. The complex of this fragment and the gyrase A protein lacks both the DNA-supercoiling and DNA-dependent ATPase activities of DNA gyrase.